Analisis Nilai Gotong Royong dalam Program Bank Sampah “Segar“ di Kelurahan Bendogerit Kota Blitar - Nurul Eka Fitria; Dwi Retnani Srinarwati; Riki Suliana RS (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Indonesia is experiencing an identity crisis that is seen from the fading values ​​such as the spirit of struggle, togetherness or mutual cooperation, concern, and unity. This study aims to describe how the value of mutual cooperation is applied between members of the management in the "Segar" Waste Bank program in Bendogerit Village, Sanawetan District, Blitar City. This study uses a qualitative method with interview, observation, and documentation techniques involving the chairman, vice chairman, secretary, and two members of the waste bank management. The data collected were analyzed by summarizing information, presenting data, and drawing conclusions. To ensure data accuracy, a comparison was made between the results of interviews, observations, and documentation so that the research results were more reliable.The results of the study show that: (1) Voluntary and responsible, seen from the active involvement of the management in collecting and sorting waste together. (2) The spirit of mutual assistance, seen in cooperation between members in carrying out waste bank activities, including dividing tasks and helping each other when facing difficulties. (3) Strengthening unity and togetherness in social life and the community environment, which is seen from the increasingly close social relations between residents. By working together in sorting waste, residents become more familiar and united. They also learn to respect each other's opinions and find solutions together when differences occur. This study proves that members of the "Segar" Waste Bank management in Bendogerit Village have implemented mutual cooperation values ​​in carrying out the activity process, by prioritizing cooperation, responsibility, and concern for the environment and the surrounding community.